2017
DOI: 10.1007/s10143-017-0825-0
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical study of pneumatized crista galli

Abstract: The literature data on the incidence of pneumatization of the crista galli based on patients' computed tomography (CT) scans ranges from 3 to 37.5%. This study investigated for the first time the incidence of crista galli pneumatization based on CT scans of human skulls. The study examined 102 randomly selected human skulls (≥20 years of age; 76 males, 26 females). Skulls were scanned in a fixed position using cone beam computed tomography (CBCT) with a field of view of 145 × 130 mm and an isotropic voxel size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 7 publications
1
35
0
1
Order By: Relevance
“…lesions in the anterior skull base and cerebrospinal fluid (CSF) leak (13,17). The FS is a nascent pneumatization in the fourth or fifth week of gestation and reaches its final size at the age of 20 years.…”
Section: Original Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…lesions in the anterior skull base and cerebrospinal fluid (CSF) leak (13,17). The FS is a nascent pneumatization in the fourth or fifth week of gestation and reaches its final size at the age of 20 years.…”
Section: Original Investigationmentioning
confidence: 99%
“…The CG, which limits the olfactory fossa medially and projects on the midline of the cribriform plate, superiorly originates from the ethmoid bone during foetal period and turns into a █ INTRODUCTION T he frontal sinus (FS) and the less common types of extrasinusal pneumatizations including the crista galli (CG) and nasal septum (NS), are in close localisation and communicate with each other if pneumatization occurs. These neighbouring structures are critical landmarks during anterior skull base surgery and endoscopic sinus surgery (ESS) (12,13). Computed tomography (CT) scan provides extremely good opportunities for the evaluation of these bony structures.…”
Section: Original Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors themselves were surprised by the high incidence, as they concluded that it was easier to judge the degree of pneumatization in human skulls, given that the tissues in spongy bone are replaced with air. 16…”
Section: Discussionmentioning
confidence: 99%
“…15 All of the previous studies investigating PCG incidence were done by analyzing the CT scans of symptomatic patients, with the exception of Mladina et al, as they analyzed the cone beam CT images of human skulls. 16…”
mentioning
confidence: 99%